A Case of Multiple Radiation-related Complications during Long-term Follow-up after Sacral Ulcer Surgery. Issue 11 (22nd November 2022) - Miyata, Riyo; Wada, Takuya; Nashihara, Sakuka; Kanagawa, Saori; Kuwahara, Masamitsu
Abstract : Summary: We report the clinical course of a patient who developed a sacral radiation ulcer 19 years after treatment for cervical cancer. The patient's postoperative course after a free latissimus dorsi muscle flap transfer was favorable, but various late radiation complications, including rectal perforation, a rectal fistula, sacral necrosis, a rectointestinal fistula, and sacroiliac joint osteomyelitis, occurred within 11 years. Plastic surgeons who treat such ulcers need to know that patients may develop other serious radiation-related complications. Being aware of these complications will allow appropriate measures to be taken and aid decisions regarding future surgical strategies. More careful assessment of sacral necrosis and bone resection may have ameliorated some of the complications. When encountering similar patients, we believe that careful magnetic resonance imagery (MRI) and intraoperative evaluation are warranted, as sacral necrosis may be detectable in some patients.